Engineering anti-individualism : a case study in social epistemology - Kerr, Eric Thomson (The University of Edinburgh, 2013)
This dissertation is a contribution to two fields of study: applied social epistemology and the philosophy of technology. That is, it is a philosophical study, based on empirical fieldwork research, of social and technical knowledge. Social knowledge here is defined as knowledge acquired through the interactions between epistemic agents and social institutions. Technical knowledge is here defined as knowledge about technical artefacts (including how to design, produce, and operate them). I argue that the two must be considered collectively both in the sense that they are best considered in the light of collectivist approaches to knowledge and in the sense that they must be considered together as part of the same analysis. An analysis solely of the interactions between human epistemic agents operating within social institutions does not give adequate credit to the technological artefacts that help to produce knowledge; an analysis of technical knowledge which does not include an analysis of how that technical knowledge is generated within a rich and complex social network would be similarly incomplete. I argue that it is often inappropriate to separate analyses of technical knowledge from social knowledge and that although not all social knowledge is technical knowledge, all technical knowledge is, by definition, social. Further, the influence of technology on epistemic cultures is so pervasive that it also forms or 'envelops' what we consider to be an epistemic agent.
Keywords: social epistemology; philosophy of technology; petroleum engineering